2013
DOI: 10.2106/jbjs.l.00474
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomic Study of the Epiphyseal Tubercle and Its Importance in the Pathogenesis of Slipped Capital Femoral Epiphysis

Abstract: The epiphyseal tubercle appears to be a major stabilizer, or keystone, of the capital femoral epiphysis and the lateral epiphyseal vessels. Its relative decrease in height and surface area with increasing age may help explain the susceptibility of individuals to SCFE in adolescence: in a stable SCFE, the physis rotates on the tubercle; however, in an unstable SCFE, the tubercle dislodges, leading to more substantial displacement of the capital femoral epiphysis and the lateral epiphyseal vessels, risking osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 18 publications
(25 reference statements)
5
64
0
1
Order By: Relevance
“…Peripheral epiphyseal extension in the proximal part of the femur has been shown to occur around the time of physeal closure with the concurrent decrease in prominence of the epiphyseal tubercle 29 . This peripheral epiphyseal extension is thought to lend stability to the physis after the epiphyseal tubercle, the primary stabilizing force against shear stress, subsides.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral epiphyseal extension in the proximal part of the femur has been shown to occur around the time of physeal closure with the concurrent decrease in prominence of the epiphyseal tubercle 29 . This peripheral epiphyseal extension is thought to lend stability to the physis after the epiphyseal tubercle, the primary stabilizing force against shear stress, subsides.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered a possible keystone for physeal stability but decreases in size and surface area during childhood and adolescence as peripheral physeal cupping increases. Liu and colleagues 22 postulate that the epiphysis internally rotates on the epiphyseal tubercle and that a widened physis could contribute to epiphyseal dislodgement. Because the lateral epiphyseal arteries are immediately adjacent to and above the epiphyseal tubercle, this could explain the low rate of osteonecrosis in chronic, stable slips (ie, minimal displacement of the lateral epiphyseal vessels) (Fig.…”
Section: Osseous and Physeal Anatomymentioning
confidence: 99%
“…62 There is no proven biomechanical or clinical advantage to the use of multiple screws versus a single screw. 60,63 Liu and colleagues 22 suggest that single in situ screw fixation should not be placed in the posterosuperior quadrant of the femoral head, the location of the epiphyseal tubercle, because the epiphysis could theoretically pivot around this single, fixed point.…”
Section: In Situ Fixationmentioning
confidence: 99%
“…Recent studies have shown that the epiphyseal tubercle reduces in all dimensions and moves to the more inferior position during skeletal growth and maturation . Those studies also indicated a concomitant peripheral growth of the epiphysis around the metaphysis, described as epiphyseal cupping.…”
mentioning
confidence: 99%
“…Despite the descriptive term slipped , displacement of the capital femoral epiphysis is unlikely to be merely a slip because of the irregular anatomy of the growth plate. In particular, an eccentric beak‐like projection at the posterosuperior aspect of the epiphysis, known as epiphyseal tubercle, has been proposed to act as a locking mechanism providing stability against the development of SCFE . Previous investigations suggested rotation of the epiphysis about the metaphysis on the eccentric pivot point of the epiphyseal tubercle as the mechanism of the displacement clinically observed in SCFE …”
mentioning
confidence: 99%